2012
DOI: 10.1371/journal.pone.0051236
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glucose Homeostasis Is Associated with Increased Serum Apelin Levels in Type 2 Diabetes Mellitus

Abstract: BackgroundApelin is an adipokine that plays a role in the regulation of glucose homeostasis and in obesity. The relationship between apelin serum concentration and dysmetabolic conditions such as type 2 diabetes (T2D) is still controversial. Aims of our study are: 1) determine the circulating levels of apelin in a large cohort of Italian subjects with T2D, T1D and in non-diabetic controls; 2) identify putative metabolic determinants of modified apelin concentrations, in order to search possible mechanism of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 27 publications
3
31
3
3
Order By: Relevance
“…Cavallo et al reported different results: Type 2, but not type 1 diabetic patients, had increased serum apelin concentrations compared to non-diabetic subjects. (Cavallo et al, 2012). These discrepancies for type 1 diabetes could be explained by the differences in the population studied (age, body mass index and diabetes duration).…”
Section: Plasma Apelin Concentrations In Diabetesmentioning
confidence: 95%
“…Cavallo et al reported different results: Type 2, but not type 1 diabetic patients, had increased serum apelin concentrations compared to non-diabetic subjects. (Cavallo et al, 2012). These discrepancies for type 1 diabetes could be explained by the differences in the population studied (age, body mass index and diabetes duration).…”
Section: Plasma Apelin Concentrations In Diabetesmentioning
confidence: 95%
“…Clinical studies have shown a promising therapeutic value for apelin, as apelin displays beneficial glucose-lowering effects in human adipose tissue and plasma apelin levels correlate with glucose (Soriguer et al 2009) and HbA1c (Dray et al 2010) levels. Apelin is linked to the pathogenesis of T2D -plasma apelin concentrations are increased in insulin-resistant patients (Li et al 2006), in type T2D patients (Cavallo et al 2012) and in morbidly obese T2D individuals (Soriguer et al 2009), perhaps indicating a compensatory role of apelin in the reduction of insulin resistance. However, conversely, plasma apelin levels are reduced in newly diagnosed T2D patients (Erdem et al 2008) and increased in T2D patients and obese non-diabetic individuals (Boucher et al 2005, Dray et al 2010.…”
Section: Metabolic Actions Of Apelin/apjmentioning
confidence: 99%
“…14 Researchers found a significant decrease in serum apelin levels after bariatric surgery in obese subjects with Type 2 diabetes in the same study group. The results from researchers' work indicate that the relationship between Type 2 diabetes and apelin is related to glucose balance, but not to obesity and other metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 82%
“…Increased apelin with hyperinsulinemia was observed in obese subjects. [14][15][16] There are studies reporting that the antioxidant capacity is impaired in obesity. 17,18 Sudden or excessive oxygen entrance into the organism due to various metabolic reasons, antioxidant defense system insufficiency or oxidant-antioxidant balance to gravitate towards the oxidant side, which then leads to occurrence of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%